2015
DOI: 10.1108/ijchm-05-2013-0194
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage in hotel human resources: recruitment, hiring and communication

Abstract: Purpose – The purpose of this study is to explore the use and non-use of social media (SM) by North American hotels for human resource (HR) activities. Design/methodology/approach – This exploratory study used an online survey and a sampling frame of 1,711 North American hotels with 300 or more rooms, excluding economy properties. With a response rate of 17.1 per cent and a defined population, data were weighted to reflect the midscale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 15 publications
1
47
0
2
Order By: Relevance
“…Roberts-Lombard (2010) also maintained that it is essential for an organization to provide effective communication tactics including internal discussion and newsletters. Nowadays, it is a popular practice to use social media for internal human resources communication (Gibbs, MacDonald, & MacKay, 2015). Research found that informal internal communication can positively affect employees' work attitude (To, Martin Jr, & Yu, 2015).…”
Section: Internal Marketing and Job Satisfactionmentioning
confidence: 97%
“…Roberts-Lombard (2010) also maintained that it is essential for an organization to provide effective communication tactics including internal discussion and newsletters. Nowadays, it is a popular practice to use social media for internal human resources communication (Gibbs, MacDonald, & MacKay, 2015). Research found that informal internal communication can positively affect employees' work attitude (To, Martin Jr, & Yu, 2015).…”
Section: Internal Marketing and Job Satisfactionmentioning
confidence: 97%
“…These data are collected from various IoT sources. The list is unlimited: (Schmidt, 2004;Mitchell, 2004) depended companies and LinkedIn (Zide, 2014;Gibbs, 2015) use a type of certified external reference to the curriculum vitae. On the other head Udemy courses won the online training competition primarily due to reporting a rather secure prove of training certificate.…”
Section: Semi-automatic Data Collectionmentioning
confidence: 99%
“…Employees who are working in this type of destination could be full-time employees, part-time employees and student employees. Full-time employees (Gibbs, et al, 2015;Mattel, 2016;Pan, 2015) have the best stability of job compared to part-time and student employees. Parttime employees (Gibbs, et al, 2015;Kattara El-Said, 2014;Lee, 2014) have a very labile job stability compared to full-time employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Full-time employees (Gibbs, et al, 2015;Mattel, 2016;Pan, 2015) have the best stability of job compared to part-time and student employees. Parttime employees (Gibbs, et al, 2015;Kattara El-Said, 2014;Lee, 2014) have a very labile job stability compared to full-time employees. Students employees (DeCenzo, et al, 2013;Greenberg, 2013;Solnet, Hood, 2008;Thompson, et al, 2016) usually work at the weekends (Thompson, et al, 2014), but could work 25 hours per week (Greenberg, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%